Analisis Penerapan Strategi Digital Marketing dalam Meningkatkan Omset Penjualan Produk Rabbani Perspektif Ekonomi Islami - Farida Arum Setiana; Naufal Kurniawan (Politeknik Baubau, 2023)
E-commerce is known as the growth of the online-based commercial world (internet), which has developed very rapidly in the last twenty years. Indonesia has enormous potential to enter this new economy. In Islamic economics, buying and selling activities or (ijarah) are said to be valid if they meet the conditions specified in the shari'a. In Banjarnegara itself, Rabbani products have spread widely among the public, not a few consumers who choose Rabbani products as the mainstay of Muslim clothing. But does the strategy implemented in marketing Rabbani products using digital marketing meet the requirements in Islamic law. The purpose of this study was to determine the application of the digital economy and its effect on increasing sales turnover of Rabbani products at the Rabbani Banjarnegara Shop. This research uses quantitative methods. The data were obtained from interviews with the shop director Rabbani Banjarnegara. The results of the study explain that the application of the digital economy in accordance with the provisions of Islamic economics at the Rabbani Banjarnegara shop greatly influences the increase in productivity, accelerates the flow of production, consumption and distribution.